2021
DOI: 10.1186/s13568-021-01269-7
|View full text |Cite
|
Sign up to set email alerts
|

In vivo evaluation of a recombinant N-acylhomoserine lactonase formulated in a hydrogel using a murine model infected with MDR Pseudomonas aeruginosa clinical isolate, CCASUP2

Abstract: Failure in the treatment of P. aeruginosa, due to its broad spectrum of resistance, has been associated with increased patient mortality. One alternative approach for infection control is quorum quenching which was found to decrease virulence of such pathogen. In this study, the efficiency of a recombinant Ahl-1 lactonase formulated as a hydrogel was investigated to control the infection of multidrug resistant (MDR) P. aeruginosa infected burn using a murine model. The recombinant N-acylhomoserine lactonase (A… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 36 publications
3
8
0
Order By: Relevance
“…Toll-like receptor 5 and inducible nitric oxide synthase) and anti-inflammatory cytokine IL-10 in zebrafish infected with Aeromonas hydrophila [ 11 ]. Similar findings were obtained in several other studies where AHLase treatment repressed Pseudomonas aeruginosa (a typical Gram-negative pathogen) infection and blocked its ability to induce inflammatory injuries and mortality of mice [ 12 , 13 ]. As a result, AHLase treatment represents a promising candidate for use as an approach against S. Typhimurium infection in animals.…”
Section: Introductionsupporting
confidence: 89%
See 1 more Smart Citation
“…Toll-like receptor 5 and inducible nitric oxide synthase) and anti-inflammatory cytokine IL-10 in zebrafish infected with Aeromonas hydrophila [ 11 ]. Similar findings were obtained in several other studies where AHLase treatment repressed Pseudomonas aeruginosa (a typical Gram-negative pathogen) infection and blocked its ability to induce inflammatory injuries and mortality of mice [ 12 , 13 ]. As a result, AHLase treatment represents a promising candidate for use as an approach against S. Typhimurium infection in animals.…”
Section: Introductionsupporting
confidence: 89%
“…In this study, we found a time-dependent alteration of ileal IL-1β, IL-8 and TNF-α expression responding to S. Typhimurium challenge, confirming a complicated impact of S. Typhimurium on the expression profile of intestinal inflammatory cytokines presumptively due to the intricate immune feedbacks of host [31]. It is known that AHLase can weaken the pathogenicity and infectivity of certain Gram-negative pathogens by restraining their physiological activities such as biofilm formation and toxin secretion [10][11][12][13][14][15]. Specially, it was found to reverse Pseudomonas aeruginosa-induced acute pneumonia by alleviating inflammatory cytokines expression in mice [12].…”
Section: Discussionsupporting
confidence: 62%
“…The efficacy of recombinant lactonase in the form of a hydrogel in controlling burn wound infections caused by a multidrug-resistant (MDR) strain of Pseudomonas aeruginosa was also demonstrated. These observations raise hopes for a new strategy to eradicate and control wound infections caused by P. aeruginosa [ 100 ]. Another interesting example is the use of the recombinant lactonase Ai-iAQSI-1 from Bacillus sp.…”
Section: Qs System Inhibitors and Degrading Enzymesmentioning
confidence: 99%
“…After completion of the study, the animals were sacrificed by intraperitoneal injection of pentobarbital sodium (1 mL/5 kg body weight). A third-degree burn wound infection model was developed with P. aeruginosa strain (PAO1) in rats as described by Sakr et al [38]. Wistar rats were grouped into 5 groups (6 rats each).…”
Section: Thermal Burn Injury Modelmentioning
confidence: 99%